Synthesis and Characterization of Activated Carbons Prepared from Agro-Wastes by Chemical Activation - Joel Brian Njewa; Ephraim Vunain; Timothy Biswick (Journal of Chemistry)
In this present study, activated carbons were prepared from rice husks and potato peels by chemical activation with 40% phosphoric acid (H3PO4). The effects of carbonization temperature and impregnation ratio were investigated with a continuous activation period. Physicochemical characteristics such as surface morphology, surface charge, and surface functional groups were assessed. According to X-ray diffraction measurements, the results showed that the activated carbons had identical pHpzc (6.8) and that the activated carbons generated were carbonaceous. The existence of hydroxyl, carbonyl, amines, aromatic, and other functional groups, which are excellent for adsorption, was revealed by surface chemistry studies. Micrographs taken with a scanning electron microscope indicated wide opening pores with a larger mesoporous surface area and many linked pores. Rice husk activated carbon outperformed potato peel activated carbon in laboratory tests. The research has shown that the agro-wastes employed in the study are possible precursors for making locally activated carbons at a low cost, thus resolving the problem of agro-waste disposal.